2016
DOI: 10.1080/1061186x.2016.1186169
|View full text |Cite
|
Sign up to set email alerts
|

PRCosomes: pretty reactive complexes formed in liposomes

Abstract: As a tribute to Pieter R. Cullis, this manuscript identifies a liposomal formulation that bears his initials: the PRCosomes. "Pretty" Reactive Complexes within liposomes were observed, while the senior author of this manuscript completed his Ph.D. thesis under Pieter's supervision. The dye (safranine) was used as a tool to measure the magnitude of the transmembrane gradient generated with liposomes. The dye's redistribution is easily detected by eye and correlates with >98% encapsulation of the dye. This obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…We confirmed that quercetin exhibits limited aqueous solubility despite heating the mixtures to 60°C (solubility is 12.33 μg/mL in water (60°C) and 38 μg/mL in HBS (60°C); data not shown). As described previously, the ability to form copper-quercetin within copper-containing liposomes is dependent on quercetin permeation across the liposomal lipid bilayer and this process is influenced by temperature [23]. Further, the rate of copper-quercetin complex formation is also likely temperature-dependent.…”
Section: Formation Of Copper-quercetin Within Copper-containing Dspc/mentioning
confidence: 71%
See 1 more Smart Citation
“…We confirmed that quercetin exhibits limited aqueous solubility despite heating the mixtures to 60°C (solubility is 12.33 μg/mL in water (60°C) and 38 μg/mL in HBS (60°C); data not shown). As described previously, the ability to form copper-quercetin within copper-containing liposomes is dependent on quercetin permeation across the liposomal lipid bilayer and this process is influenced by temperature [23]. Further, the rate of copper-quercetin complex formation is also likely temperature-dependent.…”
Section: Formation Of Copper-quercetin Within Copper-containing Dspc/mentioning
confidence: 71%
“…If a suitable intravenous formulation of quercetin was developed, issues related to bioavailability would then be addressed and perhaps suitable concentrations of quercetin in the blood could be obtained. We recently described a formulation method for poorly soluble drugs, including flavonoids like quercetin, that considers the use of compounds that can coordinate metals and nanotechnology [23]. In this report, liposomal formulations prepared based on quercetin-copper binding have been characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, polymers like poly(lactic acid) nanoparticles (183), superparamagnetic iron oxide nanoparticles (184), and mesoporous silica nanoparticles (185) have all been shown to encapsulate quercetin. Additionally, a quercetin-encapsulated liposomal product was successfully developed in our lab using a metal complexation technology that enhanced quercetin’s circulation longevity and improved its apparent solubility (186). Thus, it would be of particular interest to see if these formulations can be used to encapsulate flavopiridol to increase the therapeutic potential of the drug.…”
Section: Nanoparticulate Formulations For Flavopiridolmentioning
confidence: 99%
“…This transition metal-complexation technology has further evolved through works completed by the Bally’s group, who is now working with other founders (Ada Leung and Thomas Redelmeier), the Vice President of research (Michael Abrams), and the entrepreneurial group at UBC (e@UBC and HATCH) to lead the development of what is referred to as Metaplex technology. The Metaplex technology is an active loading platform wherein a transition metal ion gradient is established across the membrane and used as the primary driving force to accumulate drugs inside liposomes; drugs that exhibit limited water solubility, may not contain a protonizable amine, but do contain a metal binding function [60,61]. In this technology, there is clear evidence that the selected drug has a metal binding function.…”
Section: Optimization Of Liposomes For Pharmaceutical Usementioning
confidence: 99%